Initial teacher training in Colombia: reflections and perspectives from a systematic review (2022)
Educational policy in different regions of the country evidences the need to address teacher qualification processes. From this referent, this article aims to reflect on the initial teacher training in attention to pedagogical, didactic, and curricular dimensions, giving a perspective from different concepts that support the analysis. The methodological component is based on a review of documentary sources that lead to unveiling the theoretical treatment that different authors make of categories such as training, profiles, teaching competencies, and pedagogical practice. This review implies observation and content study processes that allow systematizing and arguing the findings. Among the main results, the authors agree that the initial teacher training is oriented towards the understanding of the educational reality, contemplating attributes that help them to perform adequately with marked qualities that support meaningful learning in the student. It is concluded that these processes allow emerging views on the role of the teacher in his/her practice